2006
DOI: 10.1055/s-2006-926377
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Oligo(ethylene glycol)-Terminated Icosanedisulfides

Abstract: This paper describes the synthesis of hexa(ethylene glycol) and carboxymethylhexa(ethylene glycol)-terminated alkanedisulfides 4 and 7, respectively, in which the alkylene chains are twenty-methylenes-long. The key twenty-carbon synthon, 20-bromoicos-1-ene (1), was prepared by homologation of 8-bromooct-1-ene, which was achieved via Cu(II)-catalyzed coupling of the corresponding Grignard reagent with 1,12-dibromododecane. Compounds 4 and 7 are expected to yield self-assembled monolayers (SAMs) that are more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…However, as initial attempts to isolate long chain TPP thiol compounds from the hydrolysis reaction gave significant disulfide formation, we used an initial basic pH to hydrolyze the TPP thioacetate and then rapidly decreased the pH. The bromoalkene precursors [23] , [24] for the C17 and C21 compounds were prepared by haloalkylation of the Grignard reagent prepared from 11-bromoundecene [25] . Details of the synthetic chemistry are given in the Supplemental Materials.…”
Section: Methodsmentioning
confidence: 99%
“…However, as initial attempts to isolate long chain TPP thiol compounds from the hydrolysis reaction gave significant disulfide formation, we used an initial basic pH to hydrolyze the TPP thioacetate and then rapidly decreased the pH. The bromoalkene precursors [23] , [24] for the C17 and C21 compounds were prepared by haloalkylation of the Grignard reagent prepared from 11-bromoundecene [25] . Details of the synthetic chemistry are given in the Supplemental Materials.…”
Section: Methodsmentioning
confidence: 99%
“…Johnson 11 demonstrated that in the presence of Li 2 CuCl 4 , alkyl Grignard reagents couple with only one bromide of an alkyl dibromide, with formation of the dicoupled product possible at higher temperatures and longer reaction time. Based on this and other precedents, [12][13][14] the Grignard reagent of commercially available perdeuterated bromooctane (4) was prepared and coupled to dibromooctane as the starting point for 9,9,10,10, 11,11,12,12,13,13,14,14,15,15,16,16,16-(heptadecyldeuterio)hexadecanethiol-d 17 (1, Scheme 1).…”
Section: Resultsmentioning
confidence: 99%